Use of Infant Formulas in Obstetric Hospitals - Natalia N. Korableva; Anna A. Plaksina; Victoria R. Amirova; Olga Р. Kovtun; Sergey E. Ukraintsev ("Paediatrician" Publishers LLC, 2018)
The results of a questionnaire survey of mothers on the use of infant formulas at the obstetric hospital have been presented. Possible ways to improve the situation with the use of infant formulas in term infants at the obstetric hospital have been discussed. A high frequency of the use of formulas in healthy newborns at the obstetric hospital as well as the practice of issuing formulas as a gift on discharge from the obstetric hospital have been revealed. The literature data has been given on the negative effect of both unreasonable use of formulas and the issuance of formulas as a gift on discharge on the preservation of breastfeeding. It is expected that restricting the distribution of milk formulas without proper indications will lead to an increase in the prevalence of breastfeeding.